Burnout en estudiantes de odontología: evaluación através MBI versión estudiantes - Garbin, Cléa Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP]; Santos, Renata Reis dos [UNESP]; Prado, Rosana Leal do [UNESP]; Garbin, Artênio José Isper [UNESP] (My University, 2012)
The Dentistry is considerably stressful profession in all career phases. The aim of this study was verify the presence and level of Burnout syndrome in students, to compare it in the beginning and in the end of graduation course and verify the correlation among subscales and group of social and demographic variables. Was performed study an exploratory, descriptive and cross-sectional that with the sample by 174 students coursing different periods. It was used two instrument one with social and demographic questions and MBI-SS. Among 174 students participants of study, 112 (64.37%) were girls and 62 (35.63%) were boys. There was no significant difference between dimensions of Burnout and the gender (p<0.05), professional efficacy (p<0.01) and the period whose the students were coursing. The undergraduates that are in preclinical period showed average ehigher in the two first item of scale average lower in the third item in relation to those that exercise clinically the dentistry. The level of emotional exhausting had significance. There was correlation among three levels of Burnout and the preclinical period is a fact that should be observed.

La odontología se ha configurado como una profesión estresante en todas las fases de la carrera. El objetivo de este trabajo fue averiguar la presencia y nivel del síndrome de Burnout en estudiantes, comparando al inicio y fin de la graduación y verificar la correlación entre las sub-escalas y el conjunto de variables sociodemográficas. Fue realizado un estudio exploratorio, descriptivo y transversal con una muestra de 174 estudiantes de diferentes períodos del curso, utilizándose dos instrumentos, uno con preguntas sociodemográficas y el MBI-SS. De los 174 estudiantes participantes del estudio, 112 (64.37%) eran del sexo femenino y 62 (35.63%) del sexo masculino. No hubo diferencia significativa entre las dimensiones de Burnout y el género (p>0.05). Hubo correlación entre agotamiento emocional (p<0.01), incredulidad (p<0.05), eficacia profesional (p<0,01) y el año en que el alumno está matriculado en el curso, siendo que graduandos en el período pre-clínico presentaron media más elevada en los dos primeros ítems de la escala y media inferior en el tercero ítem en relación a aquellos que actúan en la clínica. El nivel de agotamiento emocional se mostró significativo. La correlación entre los tres niveles de burnout y el período pre-clínico es un hecho que debe ser observado.
Burnout in brazilian dental students: assessment mbi – estudent survey
Keywords: Students dental; Burnout professional; Stress psychological; Students; health occupations; Estudiantes de Odontología; Agotamiento profesional; Estrés Psicológico; Empleos en Salud